2004
DOI: 10.1210/en.2003-1608
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Obesity without Insulin Resistance in Late-Onset Obesity Rats

Abstract: We describe a line of transgenic rats in which the males develop a unique autosomal dominant, late-onset obesity (LOB) phenotype. LOB males gradually accumulate fat specifically in visceral, but not peripheral, fat depots despite a normal intake of a low fat diet. LOB females normally develop only mild obesity with advanced age. However, the phenotype can be induced rapidly in young females by ovariectomy and prevented by estrogen replacement. LOB males are highly sensitive to dietary fat. Young, nonobese LOB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…In the present study, the correlation coefficients between end point FPG and baseline hs-CRP and WBC were 0.133 (p \ 0.001) and 0.134 (p \ 0.001), respectively, in subjects with baseline BMI of \25 kg/m 2 who did not use antidiabetic drugs at end point (n = 2368). Animal studies indicated that the infiltration of activated macrophages into adipose tissue and accompanied inflammation, but not increased adipose tissue mass, adipocyte size, or visceral adipose tissue mass per se, was crucial for the metabolic consequences of obesity including insulin resistance and glucose status [32][33][34][35]. Therefore, it is reasonable to think that inflammation may be associated with glucose status even in non-obese humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the correlation coefficients between end point FPG and baseline hs-CRP and WBC were 0.133 (p \ 0.001) and 0.134 (p \ 0.001), respectively, in subjects with baseline BMI of \25 kg/m 2 who did not use antidiabetic drugs at end point (n = 2368). Animal studies indicated that the infiltration of activated macrophages into adipose tissue and accompanied inflammation, but not increased adipose tissue mass, adipocyte size, or visceral adipose tissue mass per se, was crucial for the metabolic consequences of obesity including insulin resistance and glucose status [32][33][34][35]. Therefore, it is reasonable to think that inflammation may be associated with glucose status even in non-obese humans.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported a model of morbid obesity associated with an improved metabolic profile in which adiponectin acts as a peripheral starvation signal promoting the storage of triglycerides preferentially in adipose tissue and reduces the macrophage infiltration in adipose tissue preventing systemic inflammation and insulin resistance [2]. Bains et al reported a model of severe visceral obesity without insulin resistance in which the adipocyte size is not increased and the plasma level of adiponectin is increased [3]. Cinci et al described necrotic-like death of enlarged adipocyte with crownlike structure consisted of activated macrophages not only in adipose tissue of obese mice and humans but also in adipose tissue of hormone-sensitive lipase-deficient mice which is a model of adipocyte hypertrophy without obesity but with insulin resistance [4].…”
Section: Dear Sir;mentioning
confidence: 99%
“…2 Bains et al reported a transgenic model of severe visceral obesity without insulin resistance in which the adipocyte size is not increased and the plasma level of adiponectin is increased. 3 Cinci et al described necrotic-like death of enlarged adipocytes with a crown-like structure that consisted of activated macrophages not only in adipose tissue of obese mice and in visceral and subcutaneous adipose tissue of obese humans, but also in the adipose tissue of hormone-sensitive lipasedeficient mice, which is a model of adipocyte hypertrophy without obesity but with insulin resistance. 4 Kanda et al reported a transgenic model of mice with normal body and adipose tissue weight, normal adipocyte size, and normal plasma adiponectin level, which manifested macrophage infiltration into adipose tissue, insulin resistance, and glucose intolerance.…”
Section: Letter By Oda Et Al Regarding Article "Hypoadiponectinemia mentioning
confidence: 99%